Platelet Activity Associated with Concomitant Use of Clopidogrel and Proton Pump Inhibitors in Children with Cardiovascular Disease - Pasquali, Sara K. (2010)
CONTEXT: In adults with acute coronary syndrome, decreased platelet inhibition associated with concomitant use of clopidogrel and proton pump inhibitors (PPI) has been reported. OBJECTIVE: To evaluate platelet activity associated with PPI + clopidogrel vs. clopidogrel alone in children enrolled in the Platelet Inhibition in Children On cLOpidogrel (PICOLO) trial of clopidogrel in children with a cardiac condition at risk for arterial thrombosis. DESIGN: Patients 0–24 m randomized to active therapy in the PICOLO trial were included in the present analysis. Platelet aggregation inhibition at baseline and steady state were evaluated in patients taking clopidogrel + PPI vs. clopidogrel only in the overall cohort and sub-group of clopidogrel responders. RESULTS: A total of 49 patients were included (44 clopidogrel only, five clopidogrel + PPI); median age 38 days (interquartile range [IQR] 17–157 days). The majority of patients in each group had undergone systemic-to-pulmonary artery shunt. Compared with the clopidogrel group, patients in the clopidogrel + PPI group had a trend toward lower percent inhibition of maximum extent of platelet aggregation overall (median 6%, IQR 0–44% vs. 49%, IQR 19–63%, P = 0.09), and a significant reduction in the clopidogrel responders sub-group (median 25%, IQR 3–45% vs. 53%, IQR 38–65%, P = 0.04). There was no difference in percent inhibition of rate of platelet aggregation. CONCLUSIONS: Concomitant use of PPI + clopidogrel may be associated with decreased platelet inhibition in children with cardiac disease. Further study in a larger population and assessment of associated clinical outcomes is warranted.